A contribution to the development of conception of NC flexible manufacturing structures for rotational parts machining - Rekecki, Jožef; Gatalo, Ratko; Zeljković, Milan; Hodolič, Janko; Borojev, Ljubomir (Journal of Production Engineering, 2023)
This paper presents the latest information on the classification of concepts used in the design of numerically controlled (NC) flexible manufacturing structures for machining rotational parts (modules, cells, systems). The criteria used are based on research results related to part characteristics, their production processes, and research on the characteristics of developed flexible manufacturing structures.